Proceedings of GW 2007, 7th European Gesture Workshop - Dias, J.; Leitao, A. (2007)
The International Gesture Workshop is an interdisciplinary event where researchers working on human gesture-based communication present and exchange ideas and advanced research currently in progress, on gesture across multi-disciplinary scientific disciplines. This workshop encompasses all fundamental aspects of gestural studies in the field of Human-Computer Interaction and Simulation, including all multifaceted issues of modelling, analysis and synthesis of human gesture, encompassing hand and body gestures and facial expressions. A focus of these events is a shared interest in using gesture in the context of sign language analysis, understanding and synthesis. Another stream of interest is the user centric approach of considering gesture in multimodal human-computer interaction, in the framework of the integration of such interaction into the natural environment of users. In addition to welcoming submission of work by established researchers, it is the tradition of the GW series of workshops to encourage submission of student work at various stages of completion, enabling a broader dissemination of finished or on-going novel work, and the exchange of experiences in a multi-disciplinary environment. Submissions include papers, posters and demonstrations. GW2007 is the 7th European Gesture Workshop in the GW series initiated in 1996. Since this event, the Gesture Workshops have been held roughly every second year, with fully reviewed post-proceedings typically published by Springer-Verlag. In GW2007 53 contributions were received, of which were accepted 15 full papers,16 short papers and 10 as posters and demos. Two brilliant key-note speakers honoured the event with their presentations: Dr. Andrew Wilson, member of the Adaptive Systems and Interaction group at Microsoft Research, and Prof. Joaquim Jorge, Associate Professor of Computer Science at Instituto Superior Técnico (IST/UTL), the School of Engineering of the Technical University of Lisboa, Portugal.